Fibrin-blood clot as an initial stage of formation of bone regeneration after a bone fracture - O. K. Popsuishapka; N. O. Ashukina; V. O. Litvishko; V. V. Grigorjev; O. O. Pidgaiska; К. О. Popsuishapka (Regulatory Mechanisms in Biosystems, 2018)
This study focuses on mechanisms which regulate the process of fracture healing. We studied the form and position of the fibrin-blood clots (FBC) in the zone near the fragments among patients with limb fractures: macroscopically (during open surgical operations to reposition bone fragments) and using sonography. We conducted a histological and immuno-histochemical analysis of biopsy material obtained from the zone around the fracture during surgical procedures on 16 patients in 1–18 days after the fracture. We determined that the density of FBC and their form depends on the volume of damage to the periosteum-muscular fascia and the extent of the shift of fragments. In most cases, with a closed fracture, fibrin-blood clots had a spindle-shaped form. Fibrin along the periphery and in the zone between the fragments has a dense structure, and becomes cellular in central zones. The cells surrounded by fibrin partitions contain blood cells and serum. In many places, fibrin partitions had a one-direction orientation position, and the cells were oval-elongated, which indicated hydrostatic pressure in them. Proliferation of mesenchymal cells began in the vital tissues around the FBC, then during reproduction they pentrated to fibrin. Lengthwise axis of the cells was parallel to fibrin partitions. The bone trabeculae which form on the third week after fracture repeated the orientation of the fibrin partitions. It was determined that the vascular endothelial growth factor (VGEF) concentrates in fibrin and remains in it over the first week after the fracture, later it was found in endotheliocytes, fibroblasts and osteoblasts. The process of filling of the cells with around-fracture FBC lasted 12–18 days and during this period, their osteogenic differentiation occurred. Such tempi and orientation of the process is caused by fibrin with a concentration of growth factors in it. Using the results of the study, it could be assumed that the main conditions for osteogenic differentiation of cells are high concentration of VGEF in the fibrin, which initiates neoangiogenesis and internal tension of fibrin partitions. The formation of structured FBC around the ends of the fragments, which contain VGEF should be considered an initial stage of the process of forming of bone regeneration.